'The Violet Killer'—Successful Treatment of an Infant with Chromobacterium violaceum Sepsis. (2nd September 2021) - Mohammed, Jawad M; Sajana, T M; Raj, Reshma; Rachana, Babu A; Paul, George; Pillai, P Rajappan
Abstract: Chromobacterium violaceum, a facultative anaerobic proteobacterium, is isolated from water and soil in tropical areas and has been implicated in infections like septicemia, visceral abscesses, skin and soft tissue infections, meningitis and diarrhea. Chromobacterium violaceum sepsis, a rarely reported phenomenon has a very high mortality rate. Here, we report a unique case of Chromobacterium sepsis in an infant. A 48-day-old baby boy was referred to our institution with h/o fever, loose stools and reduced activity. He was intubated and referred to us in septic shock. Radiological investigations revealed multiple abscesses in the liver, spleen and kidneys. The infant was successfully treated with trimethoprim-sulfamethoxazole and ciprofloxacin.